Pengaruh Variasi Pemberian Garam pada Perendaman Telur Itik dengan Penambahan L.acidophilus Atcc terhadap Karakteristik dan Tingkat Kesukaaan pada Telur Asin - Amelia, Eca; Ningrumsari, Ida; Herlinawati, Lina (Ma'soem University, 2025)
Salted eggs are a form of processed duck eggs that are processed using the addition of a certain amount of salt. This study aims to obtain the best variety of salt administration with the addition of lactobacilus acidophilus bacteria to the characteristics of salted eggs in terms of salt content, protein cholesterol, and consumer preference. The study used a Complete Random Design (RAL) with 5 treatments and 5 replicates. The collected data was analyzed using variance analysis (ANOVA) and if there was a significant difference, it was followed by a DMRT distance. The results showed that the best variations in salt treatment with the addition of L.acidophilus ATCC are present in P1 treatment with cholesterol levels were content of 667.20 mg. protein levels were content of 13.30%, salt level were content of 3,372 % and the best values ??for color, taste, flavor and texture respectively were 4.39 (like to very very like), 3,60 (netral to like), 4.28 (like to very very like), 4.49 ( like to very very like)